2000
DOI: 10.1021/ed077p195
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Lecture-Laboratory Environment for General Chemistry

Abstract: This paper describes the physical attributes and uses of an integrated learning environment for a large-enrollment general chemistry course sequence. The room was opened in Spring Quarter 1997 and 2000 students have passed through its doors since then. The facility is one in which experimentation, collaborative student involvement, lecture, technology, and individual attention can be maximized for more effective learning (1). With it we hope to foster a healthy spirit of pedagogical experimentation in a modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…Despite the large laboratory and lecture courses not being explicitly linked in format or content (other than that they are both general chemistry courses), concurrent enrollment positively impacts student performance and retention in the lecture. These results beg the question as to what outcomes might be observed if the laboratory and lecture were explicitly aligned and taught synergistically, especially in light of studies that have reported advantages of integrated course structures (Bailey, Kingsbury, Kulinowski, Paradis, & Schoonover, 2000; Oliver‐Hoyo et al, 2004). Recall that in the studio‐style course, the laboratory and lecture were integrated and aligned in a five‐credit course, yet our results indicated no practical benefit in terms of final grades or withdrawal rates over concurrent enrollment in a nonstudio format.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the large laboratory and lecture courses not being explicitly linked in format or content (other than that they are both general chemistry courses), concurrent enrollment positively impacts student performance and retention in the lecture. These results beg the question as to what outcomes might be observed if the laboratory and lecture were explicitly aligned and taught synergistically, especially in light of studies that have reported advantages of integrated course structures (Bailey, Kingsbury, Kulinowski, Paradis, & Schoonover, 2000; Oliver‐Hoyo et al, 2004). Recall that in the studio‐style course, the laboratory and lecture were integrated and aligned in a five‐credit course, yet our results indicated no practical benefit in terms of final grades or withdrawal rates over concurrent enrollment in a nonstudio format.…”
Section: Discussionmentioning
confidence: 88%
“…Using laboratory activities to introduce concepts has been recommended by both the American Association for the Advancement of Science and the National Research Council (6, 10). The practice of coordinating laboratory activities with lecture topics has been shown to develop the understanding of concepts in both physics and chemistry (3,4,7,11).For practical reasons (class size, teaching load, laboratory space), the lecture and laboratory components may be taught as totally separate courses with the laboratory taught by a variety of instructors. Often, there may be no effort to correlate the laboratory and lecture aspects of the course.…”
mentioning
confidence: 99%
“…Variations on this style of course delivery have been implemented at a variety of institutions and in a variety of subject areas during the last few decades, including in Cal Poly chemistry and physics courses (Bailey, Kingsbury, Kulinowski, Paradis, & Schoonover, 2000; Kiste, Scott, Bukenberger, Markmann, & Moore, 2017). Early work, which established a framework for studio delivery, anecdotally reported very positive feedback from students and instructors, resulting in more widespread adoption and more rigorous evaluation of the approach (Altmiller, 1973; Apple & Cutler, 1999; Laws, 1991, 1997; Wilson & Jennings, 2000).…”
Section: Introductionmentioning
confidence: 99%